ANALISIS MASLAHAH TERHADAP PERMA NOMOR 3 TAHUN 2017 TENTANG PEDOMAN MENGADILI PERKARA PEREMPUAN BERHADAPAN DENGAN HUKUM - Mursidah, Silmi (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2018)
This Supreme Court regulation was formed because there is still widespread discrimination and gender stereotypes in the courts in Indonesia. This regulation is a maslahah hajiyah because this benefit is needed by humans, especially women who are faced the law for the convenience of their lives. If this regulation is not implemented, it will cause difficulties and negative impacts on women, both psychologically and physically. However, these difficulties do not damage the order of human life. The issuance of the Supreme Court regulation, it is expected that gender stereotypes will no longer occur in examinations in courts that can have a negative impact on women dealing with the law, both psychologically and physically, and the issuance of decisions that are gender biased. Supreme Court Rule Number 3 of 2017 concerning Guidelines for Judging the Case of Women Facing the Law, hoped that it can become a standard for judges and all judicial apparatus, in the process of examination in the courts in handling cases involving women, both as perpetrators, victims, witnesses and parties, so that the goal of eliminating all potential discrimination against women facing the law can be achieved. [Latar belakang dibentuknya peraturan Mahkamah Agung ini karena masih marak terjadi diskriminasi dan stereotip gender dalam peradilan di Indonesia. Dan peraturan yang dikeluarkan oleh mahkamah agung ini merupakan maslahah hajiyah karena kemaslahatan ini yang dibutuhkan manusia khususnya perempuan berhadapan dengan hukum untuk kemudahan hidupnya, jika tidak dilaksanakan maka akan menimbulkan kesulitan dan dampak negatif bagi dirinya baik dampak psikis maupun fisik. Namun, kesulitan tersebut tidak merusak tatanan kehidupan manusia. dengan dikeluarkannya PERMA ini diharapkan tidak lagi terjadi stereotip gender dalam pemeriksaan di pengadilan yang dapat berdampak negatif terhadap perempuan berhadapan dengan hukum baik berupa dampak psikis maupun fisik. Serta munculnya putusan yang bias gender. Diharapkan dengan dikeluarkannya PERMA Nomor 3 Tahun 2017 tentang Pedoman Mengadili Perkara Perempuan Berhadapan Dengan Hukum agar para hakim dan segenap aparatur peradilan dalam menangani perkara yang melibatkan perempuan baik sebagai pelaku, korban, saksi, dan para pihak dapat menjadi standar dalam proses pemeriksaan di pengadilan. Sehingga tujuan penghapusan segala potensi diskriminasi terhadap perempuan yang berhadapan dengan hukum dapat tercapai.]